Economic evaluation of adolescents and adults' pertussis vaccination: A systematic review of current strategies - Eder Gatti Fernandes; Camila Cristina Martini Rodrigues; Ana Marli Christovam Sartori; Patrícia Coelho De Soárez; Hillegonda Maria Dutilh Novaes (Taylor & Francis Group, 2019)
The reemergence of pertussis in the last two decades led to the introduction of adolescents and adults immunization strategies of tetanus-diphtheria-acellular pertussis vaccines (Tdap) in several countries. The health authorities must consider economic aspects when deciding to recommend and fund new programs. Here we present a systematic review of worldwide full economic evaluations of pertussis vaccination targeting adolescents or adults published from 2000. Studies were identified by searching MEDLINE, Excerpta Medica, CRD, and Lilacs databases. Twenty-seven economic evaluations of different strategies with Tdap were identified. Booster vaccination for adolescents and adults were the most frequent, followed by cocooning and pregnant women vaccination. Strategies performance varied considerably among different studies. Assumptions regarding underreporting correction, herd protection and vaccine coverage were crucial to cost-effectiveness results. Understanding the model and the parameters used is essential to understand the results, and identify the major issues important to public health decisions.